The Common Neurological Presentations and Clinical Outcomes of Coronavirus Disease 2019 in Saudi Arabia - Alkeridy, Walid A.; Alanazy, Mohammed H.; Alamri, Nada; Alqahtani, Awyshah; Alhazzani, Adel; Muayqil, Taim (Frontiers in Neurology, 2021)
Background: Neurological manifestations have increasingly become recognized in COVID-19. People from different ethnic backgrounds are experiencing different outcomes related to SARS-CoV-2 infection. Several cohort studies reported the common neurological manifestations and complications associated with COVID-19 disease around the world however, the prevalence of neurological complications associated with SARS-CoV-2 infection in the Arab countries and Saudi Arabia is still unknown. Objective: To study the prevalence, risk factors, and characteristics of the neurological complications associated with COVID-19 and their relationship with clinical outcomes. Methods: We conducted a prospective, single-center, observational, cohort study of consecutive hospitalized adults COVID-19 patients with and without neurological manifestation admitted between March 2020 until the end of December 2020. Data was collected prospectively using electronic medical records; Cases and controls were observed until they either get discharged from the hospital or died. The primary outcomes were death, survival, and survival with sequalae. Results: Among 497 patients with COVID-19, 118 patients (23.7%) had neurological complications, 94 patients (18.9%) had encephalopathy, and 16 patients (3.2%) had cerebrovascular accidents (CVA). Patients with COVID-19-related neurological complications were older and more likely to have a pre-existing neurological disease. The most common neurological syndrome associated with COVID-19 were encephalopathy (18.9%) and headache (13.7%). Pre-existing neurological disease and an elevated neutrophil count were the strongest predictors of developing any neurological complications. Death form COVID-19 was associated with age (OR 1.06, 95% CI 1.02–1.10, P = 0.001), invasive ventilation (OR 37.12, 95% CI 13.36–103.14), COVID-19-related-neurological complications (OR 3.24, 95% CI 1.28–8.21, P = 0.01), and elevated CRP level (OR 1.01, 95% CI 1.00–1.01, P = 0.01). Conclusions: COVID-19 is associated with a wide range of neurological manifestations in people living in Saudi Arabia, with older individuals and those with underlying neurological disorders being most at risk. The presence of neurological complications was associated with increased mortality and poor outcomes.